Influencing pro-environmental behaviors through visual arts: a scoping review of research designs and state of knowledge - Gbeve, Kelly; Francoeur, Virginie; Bernard, Sophie; Tanguay, Louis (Frontiers in Psychology, 2025)
BackgroundCollaboration between scientists and artists is a growing trend driven notably by the need to take action against climate change. Consequently, the role of art is evolving to serve purposes beyond communication in the scientific community. With artistic projects increasingly becoming a form of intervention to influence pro-environmental behaviors, diverse methods are being deployed to assess their influence on behavior, yet little effort has been made to document coherently this emerging diversity of research designs and learnings.ObjectiveThe aim of this study is to explore methodological approaches used to assess the effects of visual arts in promoting pro-environmental behaviors to fight climate change and determine whether some general trends can be observed.MethodologyWe conducted a scoping review to identify empirical papers published between 2001 and 2024, from which 8 studies were selected. The selected papers assessed the influence of artistic intervention on pro-environmental behaviors and its defining variables.ResultsWe found six redundant attributes in research designs. Four of them (mixed-method approach, literature-based conceptual basis, longitudinal studies, baseline environmental profiles) can help support better research designs, while two others (supplementary material, co-creation) can enhance the influence of science-art projects on behavior. We also found that, among the diverse types of art forms (movies, festivals, exhibitions, murals, immersive installation), none were able to directly and significantly affect behaviors, but they could all affect environmental attitudes or awareness to some degree.OriginalityThis scoping review stands out from prior studies by highlighting the challenges and opportunities in assessing the influence of art on pro-environmental behaviors, as well as by exploring the role of visual arts for engaging the public in such behaviors.